Reference values for dynamic radiographic measurements of lumbosacral junction width in cats - Kowalczyk, P.; Dolska, M.; Czopowicz, M.; Sterna, J.; Galanty, M. (Polish Journal of Veterinary Sciences, 2026)
Lumbosacral instability (LSI) in cats is an important condition which may precede development of degenerative lumbosacral stenosis (DLSS). Pain in the lumbosacral region often causes discomfort, changes in physical activity, behavioral disturbances, and defecation problems. The disease may be missed in its early stages in both two- and three-dimensional static examinations. Dynamic radiographic examination may reveal excessive mobility of the lumbosacral junction (LSJ) but is rarely used in feline medicine. This study aimed to determine LSJ width and its change depending on the radiographic position in healthy adult cats and to develop reference intervals (RIs). The study included 60 clinically healthy cats (23 males and 37 females) of several breeds (including 47 domestic shorthair cats), aged from 9 months to 18 years (median 17 months), weighing from 2.5 to 7.4 kg (median 3.5 kg). Dynamic plain radiography was performed in general anesthesia in three lateral positions (neutral, flexed, and extended), simulating the behavior of the LSJ during cat’s movement. RIs were determined using both parametric and non-parametric method. LSJ width was 2.0±0.2 mm in the neutral position, 2.3±0.2 mm in the flexed position, and 1.7±0.1 mm in the extended position. LSJ width measurements were not significantly different between males and females, were not significantly correlated with the cat’s age or body weight, and did not appear to differ between breeds. The RIs obtained with the two methods were almost perfectly consistent. This study provides practical grounds for the interpretation of radiographic images of the LSJ in cats and in the future may also turn out to be useful in diagnosing LSI in this species.